An overview of gold deposits in the eastern Abitibi sub province - François Robert (Canadian Institute of Mining, Metallurgy and Petroleum, 1990)
"The Eastern Abitibi Sub province (Quebec segment), contains two main types of gold deposits: the common quartz-vein type and the rare pyritic type. Both occur in areas dominated by volcanic rocks and are spatially associated with major fault zones.Quartz-vein gold deposits consist of simple to complex networks of quartz-carbonate-pyrite veins in reverse shear zones and extensional fractures. They occur in areas dominated by mafic volcanic rocks and are commonly associated with small syn- to late-tectonic porphyritic felsic intrusions. Associated alteration, which postdates peak metamorphism, is dominated by carbonatization, sericitization and pyritization of the wallrocks. These deposits formed late in the geologicalevolution of the Abitibi.Pyritic gold deposits range from deformed massive sulphide lenses to zones of syntectonic pyrite-rich veinlets and associated pyrite disseminations. These deposits occur in environments dominated by felsic volcanic rocks that are typically converted to sericite schists near the deposits. The associated pre-metamorphic aluminous alteration is now characterized by metamorphic sericite, andalusite, kyanite and chloritoid, overprinted by a late retrogression of alumino- silicates. These deposits probably represent deformed volcanogenic massive sulphide deposits, but the timing of gold introduction in these is not fully understood.The differences in geological attributes reflect significant differences in the genesis these deposits: the pyritic deposits probably have a multistage genesis, including a pre-tectonic stage, in contrast to a single stage late-tectonic genesis for the quartz-vein deposits.RESUMELa partie Est de la Sous-Province de l’Abitibi( segment québécois) renferme deux types de gites d' or: ceux de type ""veine de quartz"" et ceux, plus rares, de type ""pyriteux"". Ces deux types se trouvent dans des secteurs particulièrement riches en roches volcaniques et mantrent une association spatiale avec des zones de failles majeures.Les gites de type ""veine de quartz"" correspondent à des réseaux de complexité variable de veines de quartz-carbonate-pyrite se développant dans des zones de cisaillement inverse et des fractures de tension. Ils se concentrent dans les régions dominées par des roches volcaniques mafiques et s’associent fréquemment à de petites intrusions porphyriques felsiques syn- a tardi-tectoniques. L’altération associée ace type de glte est postérieure à la phase majeure du métamorphisme et consiste en une carbonatisation, une sericitisation et une pyritisation des épontes. La mise en place de ces gites est tardive par rapport à l'évolution géologique de l'Abitibi.Les gites d' or de type pyriteux consistent en des lentilles de sulfures massifs déformes, des zones d' abondantes veinules pyrite uses syntectoniques, et des zones de pyrite disséminée. Ces gites se retrouvent dans des empilements contenant surtout des roches volcaniques felsiques qui sont transformées en schiste à séricine pres des gisements. L’altération a l’umineuse pre-metamorphique associée a ce type de glte a donné naissance, lors du metamorphisme regional, a la sericite, a 'andal ousite, a Ia lcyanite et au chloritoi""de; par la suite, les alumino-silicates ont été affectes par une alteration retrograde tardive. Ces gites representent probablement des depOts de sulfures massifs volcan gènes déformes, mais la chronologie de la mise en place de l'or dans ceux-ci est encore mal comprise.Les caractéristiques géologiques propres à chacun de ces types de gites reflètent des conditions de formation différentes: le type ""pyriteux"" montre une histoire génétique polyphasée, incluant une étape pre-tectonique alors que le type ""veine de quartz"" s’est développe au cours d’une seule phase tardi-tectonique."